2014
DOI: 10.1021/ez5002159
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Oxidation of Piperazine by OH has a Low Potential To Form Carcinogenic Compounds

Abstract: Piperazine [HN(CH 2 CH 2 ) 2 NH, PZ] is widely recognized as an efficient solvent for carbon capture (CC). We present the first determination of the rate coefficient, k, and the branching ratios for the reaction of OH with PZ in the gas phase using the technique of pulsed laser photolysis with detection of OH by laser-induced fluorescence giving k 298 K of (2.38 ± 0.28) × 10 −10 cm 3 molecule −1 s −1 . The reaction has a negative temperature dependence parametrized as k OH+PZ = (2.37 ± 0.03) × 10 −10 (T/298) −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 28 publications
10
40
0
1
Order By: Relevance
“…N-nitrosopiperazine and N-nitropiperazine were identified and confirmed using isotopically labelled nitric oxide, with a maximum yield of nitrosamine of less than 5% observed in any samples. This is lower than, and therefore consistent with, the branching ratio determined for the aminyl radical for piperazine of 0.09 ± 0.05 (Onel et al, 2014). Using known reaction pathways for amine photooxidation (Nielsen et al, 2012b), the other photooxidation products observed in this work are likely only explained by subsequent reaction of piperazine degradation products.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…N-nitrosopiperazine and N-nitropiperazine were identified and confirmed using isotopically labelled nitric oxide, with a maximum yield of nitrosamine of less than 5% observed in any samples. This is lower than, and therefore consistent with, the branching ratio determined for the aminyl radical for piperazine of 0.09 ± 0.05 (Onel et al, 2014). Using known reaction pathways for amine photooxidation (Nielsen et al, 2012b), the other photooxidation products observed in this work are likely only explained by subsequent reaction of piperazine degradation products.…”
Section: Discussionsupporting
confidence: 82%
“…The reaction rate of PZ with OH has been calculated recently at 2.38 Â 10 À10 cm 3 molecule À1 s À1 at 298 K (Onel et al, 2014), which is considerably faster than the reaction rate constants determined for other amines with the OH radical. As a diamine with four carbon centres adjacent to nitrogen atoms, it is expected that its gas phase reaction products would also react rapidly with OH.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The concentrations of MEA and MMEA were determined using the technique developed previously using in situ absorption measurements at 185 nm. 16,18 Absorptions were converted into concentrations using the absorption cross sections of amines, s 185 nm, MEA = (8.53 AE 0.24) Â 10 À18 cm 2 molecule À1 , 16 and s 185 nm, MMEA = (9.71 AE 0.37) Â 10 À18 cm 2 molecule À1 (this work).…”
Section: Methodsmentioning
confidence: 99%
“…12 Previous studies of MEA, PZ and methylamines have shown that, once these amines are released into the atmosphere, their gas-phase processing, primarily initiated by OH radical reactions, will compete with heterogeneous uptake (lifetimes range from 15 min -1 hour at peak OH concentrations, typically 5 Â 10 6 molecule cm À3 ). [13][14][15][16][17][18] The atmospheric removal of amines by reaction with Cl atoms in gas-phase has been found to be a minor sink for amines (lifetime of B20 days for typical peak Cl concentrations, around 2 Â 10 3 atom cm À3 ). 19,20 A major concern with PCCC is the impact of carcinogenic nitrosamines (R 2 N-NO) and nitramines (R 2 N-NO 2 ), formed in the gas-phase processing of amines, on human health.…”
Section: Introductionmentioning
confidence: 99%